2021
DOI: 10.3389/fenvs.2021.716516
|View full text |Cite
|
Sign up to set email alerts
|

A Field Guide for Monitoring Riverine Macroplastic Entrapment in Water Hyacinths

Abstract: River plastic pollution is an environmental challenge of growing concern. However, there are still many unknowns related to the principal drivers of river plastic transport. Floating aquatic vegetation, such as water hyacinths, have been found to aggregate and carry large amounts of plastic debris in tropical river systems. Monitoring the entrapment of plastics in hyacinths is therefore crucial to answer the relevant scientific and societal questions. Long-term monitoring efforts are yet to be designed and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Moreover, the larger the sub-catchment area, the more riparian vegetation plays a role in litter accumulation. In this regard, we report here that, for instance, plastic bags were mostly found trapped in the vegetation at the riverside, which is known to act as a trap for floating materials (Schöneich-Argent et al, 2020;Schreyers et al, 2021;van Emmerik and Schwarz, 2020;.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, the larger the sub-catchment area, the more riparian vegetation plays a role in litter accumulation. In this regard, we report here that, for instance, plastic bags were mostly found trapped in the vegetation at the riverside, which is known to act as a trap for floating materials (Schöneich-Argent et al, 2020;Schreyers et al, 2021;van Emmerik and Schwarz, 2020;.…”
Section: Discussionmentioning
confidence: 76%
“…Abundance, composition and distribution of RAM are influenced by the cumulative effects of an array of environmental characteristics including, among the others, the presence of floating and riparian vegetation (Cesarini and Scalici, 2022;Schreyers et al, 2021;Windsor et al, 2019), tidal influence, seasonal changes of the water level and flow rate (Battulga et al, 2019;Vriend et al, 2020b), and curvature and shape of the river (Calcar and van Emmerik, 2019). Moreover, RAM accumulation can be also influenced by several anthropogenic pressures like land use (Cowger et al, 2019;McCormick and Hoellein, 2016), fluvial navigation and the presence of hydraulic infrastructures (Calcar and van Emmerik, 2019;Mihai, 2018;Schirinzi et al, 2020), human population and road density (Battulga et al, 2019;Jambeck et al, 2015;McCormick and Hoellein, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For visually capturing the abundance and distribution of water hyacinths, satellite based synoptic view explicitly facilitate the in-situ measurements, which otherwise makes it tedious from a eld measurement perspective (Schreyers et al, 2021). Satellite imagery can distinctly identify the spectral signals as well as assess the spatial spread of water hyacinth in the area of interest (AOI) i.e., Deepor beel wetland.…”
Section: Satellite Datasets Usedmentioning
confidence: 99%
“…The spectral resemblance of the water hyacinths and other aquatic vegetation within the water body is ambiguous in nature, however minimizing this effect is a crucial step for an accurate mapping. Masking of the area covered by water on the imagery along with eld ground truthing (for the water hyacinth vegetation) can provide relatively sound results (Schreyers et al, 2021). In the electromagnetic spectrum, highest re ectance peak, for water hyacinth vegetation, is observed for the Near-Infrared (NIR) wavelengths of light (∼850 nm), and absorption in the red (∼660 nm).…”
Section: Image Pre-processing and Classi Cation Analysismentioning
confidence: 99%
“…Previous findings have suggested that plastics persist throughout riverine ecosystems with a large fraction found suspended in the water column (Hohenblum et al, 2015;Broere et al, 2021). Presently, plastic monitoring in the water column of rivers is time consuming as plastics are mainly collected with nets, then sorted and counted manually, or visually identified in situ (Cheshire et al, 2009;OSPAR Commission, 2010;Morritt et al, 2014;Schöneich-Argent et al, 2020;Schreyers et al, 2021). Riverine plastic pollution categorization involves large volumes of waste, thus time-and cost-effective techniques for long-term monitoring are needed ( Van Emmerik et al, 2020b;Schöneich-Argent et al, 2020;Meijer et al, 2021;Van Emmerik et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%